Transcranial Cavitation Detection in Primates during Blood-Brain Barrier Opening – A Performance Assessment Study - Wu, Shih-Ying (2014)
Focused ultrasound (FUS) has been shown promise in treating the brain locally and noninvasively. Transcranial passive cavitation detection (PCD) provides methodology of monitoring the treatment in real time, while the skull effects remain a major challenge for its translation to the clinic. In this study, we investigated the sensitivity, reliability, and limitations of PCD through primate (macaque and human) skulls in vitro. The results were further correlated with the in vivo macaque studies including the transcranial PCD calibration and real-time monitoring of BBB opening, with magnetic resonance imaging assessing the opening and safety. The stable cavitation doses using harmonics (SCD(h)) and ultraharmonics (SCD(u)), the inertial cavitation dose (ICD), and the cavitation signal-to-noise ratio (SNR) were quantified based on the PCD signals. Results showed that through the macaque skull the pressure threshold for detecting the SCD(h) remained the same as without the skull in place, while it increased for the SCD(u) and ICD; through the human skull, it increased for all cavitation doses. The transcranial PCD was found reliable both in vitro and in vivo when the transcranial cavitation SNR exceeded the 1-dB detection limit through the in vitro macaque (attenuation: 4.92 dB/mm) and human (attenuation: 7.33 dB/mm) skull. In addition, using long pulses enabled reliable PCD monitoring and facilitate BBB opening at low pressures. The in vivo results showed that the SCD(h) became detectable at pressures as low as 100 kPa; the ICD, at 250 kPa while it could occur at lower pressures; the SCD(u), at 700 kPa and was less reliable at lower pressures. Real-time monitoring of PCD was further implemented during BBB opening, with successful and safe opening achieved at 250–600 kPa in both the thalamus and the putamen. In conclusion, this study shows that transcranial PCD in macaques in vitro and in vivo as well as humans in vitro is reliable by improving the cavitation SNR beyond the 1-dB detection limit.